California Pro-Life Council questionnaire (1976)
This document is a 1976 primary election questionnaire from the California ProLife Council sent to political candidates. It asks whether the candidate would support a U.S. constitutional amendment guaranteeing the right to life from conception to natural death, except when abortion is an unavoidable result of a medical procedure necessary to save the mother's life. Candidates are instructed to indicate "yes" or "no," provide additional comments on their position and record, and supply identifying information before returning the form by the stated deadline.